Corrosion Inhibition of Mild Steel in HCl using Methylene Blue as Inhibitor - Ibisi N.E.; Amadi S.O. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The corrosion inhibition of mid-steel in 5M HCl solution in the absence and presence of methylene blue (MB) was studied at 300c using the hydrogen evolution technique (gasometric). The results indicate that the methylene blue functioned as a good inhibitor in acidic medium. The inhibition efficiency increased with increase in the concentration of methylene blue. Inhibition therefore, is attributed to the adsorption of the inhibitor on the surface of the mild steel thereby eliminating site for corrosion. The experimental data fit into the Langmuir, Freundlich and Temkin adsorption Isotherms.